Ru, Pd doped WO3 nanomaterials: a synergistic effect of noble metals to enhance the acetone response properties - Kodam, Pavan M.; Ghadage, Pandurang A.; Nadargi, Digambar Y.; Shinde, K. P.; Mulla, Imtiaz S.; Park, J. S.; Suryavanshi, Sharad S. (Ceramics International, 2022)
Noble metals (NMs) have an enormous impact on the intrinsic properties of the metal oxides. We report the synergistic effect of Ruthenium (Ru) and Palladium (Pd) noble metals on the enhancement of gas sensing properties of pure tungsten oxide (WO3). The gas sensing material is synthesized by simple and straight forward precipitation route, and its physico-chemical analyses are determined using XRD, FESEM, TEM/HRTEM, FFT, UV-Vis, XPS, EDAX, and BET measurements. Use of the developed material as a gas sensor is evaluated using several target gases (oxidizing as well as reducing), with acetone showing the best selectivity. The noble metal doping and hence catalytic action improved the gas response qualities. The synergistic effect of Ru and Pd on WO3 gas response properties are identified, where the effect is 99.80% sensitivity, and lower response/recovery time (10 s and 2 min) at 300 degrees C operating temperature. Nonetheless, the sensors displayed better gas sensing properties even at lower operating temperatures ranging from 200 to 275 degrees C. In addition, the synergistic effect has displayed the dramatic enhancement in the sensitivity to 76.44% at barely 10 ppm acetone concentration. This particular result will undoubtedly be helpful for diagnostic purpose of diabetic patients, and a strong candidate for prospective gas sensing applications, particularly acetone.
Keywords: Acetone vapours; Precipitation route; Ru -Pd doping; synergistic effect; WO3

Reduced graphene oxide/tungsten oxide (rGO/WO3): a versatile nanocomposite for enhanced detection of acetone - Patil, Abhijeet P.; Gaikwad, Mayur A.; Nadargi, Jyoti D.; Shaikh, Hamid; Alam, Mohammad Asif; Tamboli, Mohaseen S.; Kim, Jin Hyeok; Mulla, Imtiaz S.; Suryavanshi, Sharad S. (Journal of Materials Science-Materials In Electronics, 2024)
In this study, we report a straightforward method for synthesizing semi-cubical nanostructures of tungsten trioxide (WO3) loaded with reduced graphene oxide (rGO) via a hydrothermal approach. Furthermore, the systematic investigations were made towards the improved gas sensing capabilities of these nanostructures for acetone. The use of semi-cubical rGO/WO3 nanostructures demonstrate the provision of efficient gas diffusion routes via a meticulously arranged mesoporous framework. Hence, it leads to a significant improvement in the sensing response towards acetone. The analysis of the sensing capabilities demonstrates that the response of the sensor is influenced by variations in operating temperature and gas concentration. It is seen that the inclusion of rGO not only enhances the sensing response but also gives quick response and recovery, which are measured to be 12 and 33 s, respectively. The WO3 sensor loaded with 0.1 wt% rGO demonstrates a discerning reaction to acetone, exhibiting a high response of 93.60% than that of the unmodified WO3 sensor (76.30%). The gas sensing properties are explained through the role of rGO and the structural and morphological properties of the developed nanostructures.